Hard Hit by El Nino : Experiences, Responses and Options for Malawi - Botha, Blessings Nyanjagha (World Bank, Washington, DC, 2018)
In Malawi, the impact of extreme weather events has significantly contributed to the recurrent crises of food insecurity. The extreme weather events have shifted the country’s focus from improving agricultural productivity and resilience to ensuring survival, with most resources devoted toward humanitarian assistance. The country is highly exposed to multiple hazards that cause widespread shocks. In recent years, the country faced successive and compounding climatic shocks: from the worst flood in 50 years in 2015, to the strongest El Niño event in 35 years in 2016. This prompted declaration of a state of disaster and left 39 percent of the country (6.7 million people) at risk of food insecurity during the 2016/17 consumption period. The El Niño–Southern Oscillation (ENSO) is the most important driver of climatic variability in Malawi. Even though El Niño occurrences are predicted to increase in frequency, the Government of Malawi’s (GoM) actions are inadequate, as disaster management is largely reactive than proactive.The agriculture sector, which contributes 30 percent to Malawi’s gross domestic product (GDP), has been severely affected by the extreme weather events. This is amplified by the overreliance on single-season rainfed agricultural production, dominated by maize-based systems that are vulnerable to climatic shocks. The agriculture sector incurs huge losses when disaster strikes, amounting to approximately 89 percent of the total losses. In response to reduced production of most crops, average prices have generally increased, fueling inflation and reduced agricultural growth, and ultimately adversely impacting the economy at large. The Government of Malawi (GoM) has responded by putting in place various policies and coordinating institutions or structures to address extreme weather events, including increasing its responsibility for responding to the aftermath e.g. increasing support to maize purchases. However, its policies are fragmented, with inadequate resources to translate them into action, while capacity gaps further cripple increased coordination requirements. In view of this, efforts have not translated into sustained results when disasters recur, creating a vicious cycle of food insecurity and vulnerability. This analytical work was undertaken to assist the GoM to strengthen its efforts toward effectively responding to extreme weather-related events, especially El Niño and La Niña phenomena. Specifically, the study aims to provide a critical review of how the country has responded to recent extreme weather events, draw lessons for future response planning, and identify gaps and options to strengthen preparedness and response to El Niño, La Niña, and similar weather events. The study used a combination of primary and secondary data collected from July to September 2017. Primary data were collected through focus group discussions and key informant interviews in Malawi’s 15 disaster-prone districts. Secondary data included a review of various policies, research reports, and other documents.